CHILDFREE BY CHOICE : MENJELAJAHI MOTIVASI ,TANTANGAN,DAN PERSEPSI SOSIAL (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Child free is a choice of a person or couple not to have children or offspring for various reasons, child free itself is certainly chosen with various considerations such as, economic aspects, mental / health, and freedom, now in Indonesia child free has begun to be crowded and hot in the discussion, of course the choice not to have children will reap cons both from his family and his environment, we chose a theme entitled "Childfree by choice. Exploring motivations, challenges, and social perceptions, you try to explore what are their reasons and motivations for this child free view and choose it and what are the challenges and social perceptions that will occur this is what we will focus on in this article. We have seen several articles and journals about child free in several studies, and we used the SLR (Systematic Literature review) method from what we got Childfree is a life choice made for certain reasons. Although this view is contrary to social and religious values, the phenomenon of childfree is increasingly recognized and accepted by society. The decision to go childfree is considered to be a decision taken jointly by the couple and the parents of both parties. The reasons underlying this decision include concerns related to child development, personal, economic and environmental issues. Child free must be analyzed and understood more deeply as a choice that can be accounted for.